Religious tourism in Christian sanctuaries: the implications of mixed interests for the communication of the faith - Wisniewski, Lukasz (Church, Communication and Culture, 2018)
Christian sanctuaries are places of a unique contact between man and God. This article deals with shrines in Europe and North America (Washington, Guadalupe, Lourdes, Fatima, Czestochowa, Assisi, San Giovanni Rotondo, Santiago de Compostela). Such shrines have long been meeting places for people on a pilgrimage of faith. This tradition still exists today, even if many sanctuary visitors primarily want to explore the cultural heritage or discover the sources of spirituality. This new trend has consequences for the pastoral services on-site. Therefore, it is significant that the Catholic Church's Magisterium since the second half of the 20th century has invited the shrine rectors to make their sacred sites a place of the New Evangelization. This article explains how the message of faith that is communicated to believers by pastoral care, sacramental ministry and proclamation of the word of God could also be offered to cultural tourists and nonbelievers, in particular through art, architecture, music and the works of mercy. Here the study offers insights into how the recent Church documents emphasized Christian hospitality as a tool of evangelization. Finally, we analyze the new media communications of shrines (websites, social media channels) as opportunities for proclaiming the Gospel message.